Development of true orthophotomaps of the fortified settlement at Biskupin, Site 4, based on archival data. - Zawieska, Dorota; Markiewicz, Jakub; Kopiasz, Jarosław (Archaeological Prospection, 2019)
This article describes the results of the project to reconstruct a Lusatian culture fortified settlement at Biskupin (one of the most well‐known archaeological sites in Poland) using various archival data. This research work will cover Site 4 at Biskupin, based on the archaeological examinations conducted there during the period 1934–1939, i.e. pre‐war photographs acquired from different heights, e.g. from a captive balloon (maximum height up to 150 m) from a blimp (at a height of 50 to 1000/1100 m) and from an aeroplane (at a height of 200 m, 300 m and up to 3 km). Modern technology enables the creation of true orthophotomaps, which are used to amend the missing drawing documentation created in situ during pre‐war archaeological excavations. The orientation of archival, non‐metric photographs acquired from different flight heights for interpretation purposes (but not for metric documentation purposes) was performed using both structure‐from‐motion algorithms (implemented in the Agisoft PhotoScan software) and the conventional approach based on Gruber points. The investigated area was divided into four sections and all the images were orientated in one reference system, which was defined during the surveys and excavations. The estimated orientation accuracy at the check points was in the range of 0.1 to 0.4 m. The final true orthophotomaps, with reference to the maintained vector drawing, were analysed. The estimated relative error was smaller than 3%. The photogrammetric products will allow for a better understanding of construction as a whole, and for the recognition of particular structures, in particular, by taking into account functional and chronological aspects.